Low BMI, blood calcium and vitamin D, kyphosis time, and outdoor activity time are independent risk factors for osteoporosis in postmenopausal women - Tang, Guo; Feng, Long; Pei, Yu; Gu, Zhaoyan; Chen, Tingting; Feng, Zeguo (Frontiers in Endocrinology, 2023)
Aim: To explore the risk factors of osteoporosis in postmenopausal women in China. Method:This study collected all patient data from January 2014 to December 2015. Basic information and questionnaires were collected from 524 postmenopausal women in Sanya and Hainan Province.The questionnaire was administered to the enrolled participants by endocrinologists. Biochemical parameters were measured using fasting blood samples, and bone density was measured by dual energy X-ray absorptiometry at the department of radiology of Hainan hospital, PLA General Hospital. Participants with an R-value of ≤-2.5 were diagnosed with osteoporosis. After deleting missing values for each factor, 334 participants were divided into the osteoporosis (n=35) and non-osteoporosis (n=299) groups according to the R-values. Results: The participants had a median age of 60.8 years (range: 44-94 years). Among the 334 postmenopausal women included in this study, 35 (10.5%) were diagnosed with osteoporosis. Univariate analysis showed statistically significant differences in age, BMI, type of work, alkaline phosphatase, years of smoking, blood calcium levels, kyphosis, fracture, and asthma between the two groups (P<0.05).In addition, multivariate logistic analysis showed that age (odds ratio [OR]: 1.185, 95% confidence interval [CI]: 1.085-1.293, P<0.001) and kyphosis times (OR:1.468, 95% CI:1.076-2.001, P=0.015) were positively correlated with postmenopausal osteoporosis, whereas BMI (OR: 0.717, 95% CI: 0.617-0.832, P<0.001), blood calcium levels (OR: 0.920, 95% CI: 0.854-0.991, P=0.027), vitamin D levels (OR: 0.787, 95% CI: 0.674-0.918, P=0.002), and outdoor activity time (OR: 0.556, 95% CI: 0.338-0.915, P=0.021) were negatively correlated with postmenopausal osteoporosis. Conclusion: Low BMI, blood calcium and vitamin D levels, kyphosis time, and outdoor activity time are independent risk factors for osteoporosis in postmenopausal women.